Recurrent fever-associated acute liver failure and cranial dysmorphism in children caused by RINT1 gene mutations: a rare case report - Cui, Yanfei; Abudu, Fawudan; Simijiang, Yipaguli (Frontiers in Pediatrics, 2025)
Mutations in the RINT1 gene represent a rare genetic cause of recurrent fever-associated acute liver failure (ALF) accompanied by skeletal abnormalities in infants and children. We report the case of a 9-month-old infant presenting with multisystem involvement, primarily characterized by recurrent fever-associated ALF and cranial dysmorphism, due to compound heterozygous mutations in the RINT1 gene. The patient exhibited abnormal liver function tests and coagulation dysfunction following febrile episodes. Over a period of more than one year, the patient initially experienced two episodes of acute liver injury, followed by two episodes of ALF, with progressively worsening clinical manifestations. Whole-exome sequencing (WES) identified compound heterozygous variants in the RINT1 gene (exons 12–14 deletion; intron 11, c.1672-1G > T, p.?), consistent with a diagnosis of infantile liver failure syndrome-3 (ILFS3). Between episodes, liver function failed to return fully to baseline and was accompanied by growth retardation, delayed psychomotor development, cranial dysmorphism, and beak-like deformities of vertebral bodies. This case highlights the critical role of RINT1 mutations in the pathogenesis of recurrent fever-associated ALF and emphasizes the importance of recognizing associated skeletal developmental abnormalities, including cranial dysmorphism. Early genetic diagnosis and prompt antipyretic intervention may mitigate liver injury and improve long-term outcomes. By documenting cranial dysmorphism in this context, we aim to expand the recognized phenotypic spectrum of ILFS3 and improve clinical awareness among pediatricians and geneticists.